Clinicopathological features of fast eGFR decliners among patients with diabetic nephropathy. Issue 1 (4th June 2020) - Furuichi, Kengo; Shimizu, Miho; Yamanouchi, Masayuki; Hoshino, Junichi; Sakai, Norihiko; Iwata, Yasunori; Toyama, Tadashi; Kitajima, Shinji; Hara, Akinori; Yuzawa, Yukio; Kitamura, Hiroshi; Suzuki, Yoshiki; et al.
Abstract : Introduction: The speed of declining kidney function differs among patients with diabetic nephropathy. This study was undertaken to clarify clinical and pathological features that affect the speed of declining kidney function in patients with diabetic nephropathy. Research design and methods: This study was design as multicenter retrospective study. The subjects (377 patients with diabetic nephropathy diagnosed by kidney biopsy at 13 centers in Japan) were classified into three groups based on the estimated glomerular filtration rate (eGFR) declining speed. The eGFR increasing group, the control group, and the eGFR declining group were divided at 0 and 5 mL/min/1.73 m 2 /year, respectively. Characteristics of clinicopathological findings of declining kidney function were evaluated. Results: The mean observation period of this study was 6.9 years. The control group, the eGFR increasing group, and the eGFR declining group included 81, 66, and 230 patients, respectively. The incidences of composite kidney events represented by 100 persons/year were 25.8 in the eGFR declining group and 2.0 in the eGFR increasing group. After adjustment for age, sex, systolic blood pressure, hemoglobin, and urinary albumin levels, three clinicopathological findings (urinary albumin levels, presence of nodular lesion, and mesangiolysis) were risk factors for inclusion in the eGFR declining group (the ORs were 1.49, 2.18, and 2.08, respectively). In contrast, the presence of subendothelial space widening and polar vasculosis were characteristic findings for inclusion in the eGFR increasing group (the ORs were 0.53 and 0.41, respectively). Conclusions: As well as urinary albumin elevation, nodular lesion and mesangiolysis were characteristic pathological features of patients with fast declining kidney function.